2020
DOI: 10.1111/cdoe.12539
|View full text |Cite
|
Sign up to set email alerts
|

Atraumatic restorative treatments improve child oral health‐related quality of life: A noninferiority randomized controlled trial

Abstract: Objectives Management of dental caries under dental general anaesthesia (DGA) in young children improves their quality of life. A randomized controlled trial was undertaken to test the changes in oral health‐related quality of life among children treated under a DGA or managed using the Atraumatic Restorative Treatment and Hall crown approaches (ARTs). Methods Children scheduled for a DGA for the management of dental caries after assessment at the Oral Health Centre of Western Australia were invited to partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 32 publications
(80 reference statements)
0
22
0
Order By: Relevance
“…Some participants in the DGA sought other treatment options for various reasons including concern about costs and safety of DGA. A qualitative study found that parents felt troubled and found difficult to accept DGA as the treatment option for their child 21 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some participants in the DGA sought other treatment options for various reasons including concern about costs and safety of DGA. A qualitative study found that parents felt troubled and found difficult to accept DGA as the treatment option for their child 21 31 …”
Section: Discussionmentioning
confidence: 99%
“…The trial investigated the provision of comprehensive care including tooth extractions and pulp treatment in a primary care setting in order to minimize the need for a DGA. The findings with respect to clinical effects, impacts on child oral health‐related quality of life (COHRQoL) and parent/carer perspectives on care provided to their child have been reported 20–22 . The specific objectives of the RCT were to: (a)estimate average probability of successfully managing the dental treatment of the child; (b)identify changes in COHRQoL; (c)determine parents' views on the care provided to their child; (d)investigate if the ART/HT offers good value‐for‐money, defined as less costly with improved effectiveness or cost neutral with improved effectiveness. …”
Section: Introductionmentioning
confidence: 99%
“…Findings related to clinical outcomes and changes in child oral health-related quality of life have already been reported [8,9].…”
Section: Discussionmentioning
confidence: 86%
“…While acknowledging the use of other options such as pharmacological sedation and protective stabilisation in managing dental treatment of children [12], this study reports on P/C views within a randomised trial of the management of their child's dental caries under a DGA and an alternative minimally invasive approach using the Atraumatic Restorative Treatment and the Hall technique (ART/HT) after their child had been recommended a DGA. The findings with respect to clinical outcomes and impact on COHRQoL have been reported [8,9]. The aim of this study was to elicit P/C views on approach to care with the DGA within a publicly funded care system and a minimally invasive alternative approach to the DGA.…”
Section: Introductionmentioning
confidence: 99%
“…The findings lend further support for the use of ARTs in the delivery of dental services to young children. The approach had enabled the provision of dental treatment in a primary care setting and improved the oral health-related quality of life of young children recommended for dental general anaesthesia (Arrow and Forrest 2020a, 2020b). However, there has been no evidence of its effectiveness in a remote Aboriginal Australian context.…”
Section: Discussionmentioning
confidence: 99%